Collaborative research into the next generation spatial infrastructure - Chan, T.; West, Geoff; McMeekin, David; Woodgate, P.; Loughrey, P. (Surveying and Spatial Sciences Institute, 2013)
The Spatial Infrastructure Program (Program 3) is one of three core research programs of the CRCSI. Owing to a delay in research strategy development, the CRCSI built a project team to deliver a timely Program 3 research program. Within a nine-month period, the team engaged with over 100 key stakeholders and CRCSI participants, which were interested in working collaboratively, directly and indirectly, through Program 3 to develop the next generation spatial infrastructure to allow them to better deliver their services. The team established broad stakeholder consensus on the research direction and got approval for a research strategy. An integrated research proposal was put forward based on the interests of the key stakeholders and participants of the CRCSI.The key drivers of the Program were that the next generation spatial infrastructure had to be based on a web architecture that supported automation and step-change usability throughout the system. The underpinning disciplines were the Semantic Web, Supply Chains and Artificial Intelligence.In order to make the research outputs more relevant to the participants, one approach the program has adopted is to develop a research platform, based on the best-of-breed infrastructures available in Australia and New Zealand. This approach is complemented by an improved project governance arrangement involving an agile approach to research management. This is to ensure that the research outputs are relevant and that project participants can test the outputs in operational environments to determine suitable utilisation pathways for incorporation into existing spatial infrastructures.